Diagnostic Yield of Echocardiography in Syncope Patients with Normal ECG. (4th January 2016) - Chang, Nai-Lun; Shah, Priyank; Bajaj, Sharad; Virk, Hartaj; Bikkina, Mahesh; Shamoon, Fayez
Abstract : Aim . This study aimed to assess the role of echocardiography as a diagnostic tool in evaluating syncope patients with normal versus abnormal electrocardiogram. Methods . We conducted a retrospective study of 468 patients who were admitted with syncope in 2011 at St. Joseph's Regional Medical Center, Paterson, NJ. Hospital records and patient charts, including initial emergency room history and physical, were carefully reviewed. Patients were separated into normal versus abnormal electrocardiogram groups and then further divided as normal versus abnormal echocardiogram groups. Causes of syncope were extrapolated after reviewing all test results and records of consultations. Results . Three hundred twelve of the total patients (68.6%) had normal ECG. Two-thirds of those patients had echocardiograms; 11 patients (5.7%) had abnormal echo results. Of the aforementioned patients, three patients had previous documented history of severe aortic stenosis on prior echocardiograms. The remaining eight had abnormal but nondiagnostic echocardiographic findings. Echocardiography was done in 93 of 147 patients with abnormal ECG (63.2%). Echo was abnormal in 27 patients (29%), and the findings were diagnostic in 6.5% patients. Conclusions . This study demonstrates that echocardiogram was not helpful in establishing a diagnosis of syncope in patients with normal ECG and normal physical examination.